TINJAUAN YURIDIS MENGENAI PENERAPAN HAK MENDAHULU (PREFEREN) DALAM PENAGIHAN UTANG PAJAK PADA KASUS KEPAILITAN (Studi Kasus Putusan Mahkamah Agung Nomor 168 PK/Pdt.Sus/2012) - Putri Kemala Sari (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2018)
Taxes are a compulsory contribution to a country that is indebted by an individual or a coercive body under the Act with no direct remuneration and used for the purposes of the state for the greatest possible prosperity of the people. The provision indicates that the position of the state or in other words referred to as the fiscal gets a very special place to regulate all arrangements concerning taxation and this is also marked by the nature of the inherent force to the taxpayer to pay off the tax debt. As regulated in Law Number 16 Year 2009 (hereinafter referred to as UU KUP), Article 21 paragraph (1) which reads "The State has the prior right to tax debt on goods belonging to the tax penanggungan". The purpose of this study is to examine how the introduction of the provision of State Owned Rights to tax debt by taxpayers. The method used is normative juridical approach method with descriptive analytical research specification. The result of the research shows that based on the analysis done by the writer on the Decision of Supreme Court Number 168 PK / Pdt.Sus / 2012 in the case of bankruptcy, asserted that not necessarily the provision of Article 21 paragraph (1) UU KUP gives space as big as to the state as the body having a privileged position to receive tax deductible by the taxpayer.Keywords: Preferen, Tax, Tax Debt, Tax Colection